2014
DOI: 10.1074/jbc.m113.523936
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Ovarian Tumor Domain-containing Protein 1 (OTU1) Binding to p97/Valosin-containing Protein (VCP)

Abstract: Background: Ovarian tumor domain-containing protein 1 (OTU1) acts as a deubiquitinating enzyme in the endoplasmic reticulum-associated degradation (ERAD) pathway by associating with valosin-containing protein (VCP). Results: One OTU1 binds to a VCP hexamer with a K D of 0.71 M. Conclusion:The 39 GYPP 42 (S3/S4) loop of OTU1 is critical for interaction with VCP. Significance: This is the first structural study of VCP and OTU1 complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 48 publications
0
26
1
Order By: Relevance
“…Recently, we reported that the UBXL domain of OTU1 adopts a ubiquitin-like fold and binds at the interface of two subdomains of the N domain of VCP using the S3/S4 loop from the complex structure of the N domain of VCP and the UBXL domain of OTU1 (Kim et al, 2014). However, our electron-microscopy (EM) results on the full-length proteins show that only one OTU1 binds to a VCP hexamer.…”
Section: Introductioncontrasting
confidence: 45%
“…Recently, we reported that the UBXL domain of OTU1 adopts a ubiquitin-like fold and binds at the interface of two subdomains of the N domain of VCP using the S3/S4 loop from the complex structure of the N domain of VCP and the UBXL domain of OTU1 (Kim et al, 2014). However, our electron-microscopy (EM) results on the full-length proteins show that only one OTU1 binds to a VCP hexamer.…”
Section: Introductioncontrasting
confidence: 45%
“…Of these, only the p97 UFD1-NPL4-OTU1 complex has been studied in more detail. In vitro binding and EM studies showed that only one OTU1 molecule is recruited into the p97 UFD1-NPL4 complex [58], thus forming an oligomer with a stoichiometry of 6:1:1 similar to the p97 UFD1-NPL4-FAF1 complex discussed above. However, no hierarchical binding was observed, indicating an independent binding mode and suggesting that hierarchical binding may be restricted to substrate-recruiting cofactors of the UBA-UBX type.…”
Section: Higher Order Assembliesmentioning
confidence: 99%
“…In addition to the UBA-UBX proteins discussed above, the UFD1-NPL4 heterodimer was also found in quaternary complexes with p97 and Otu1/YOD1 [51,58], NUB1L [74] and SelS/VIMP [66]. Of these, only the p97 UFD1-NPL4-OTU1 complex has been studied in more detail.…”
Section: Higher Order Assembliesmentioning
confidence: 99%
See 2 more Smart Citations